Assessment of rapid evaporative ionization mass spectrometry (REIMS) to characterize beef quality and the impact of oven temperature and relative humidity on beef - Gredell, Devin, author; Woerner, Dale, advisor; Belk, Keith, committee member; Engle, Terry, committee member; Prenni, Jessica, committee member; Heuberger, Adam, committee member (Colorado State University. Libraries, 2018)
The objective of experiment 1 was to evaluate the ability of rapid evaporative ionization mass spectrometry (REIMS) to predict beef eating quality characteristics. Striploin sections (5 cm in thickness; N = 292) from 7 beef carcass types (Select, Low Choice, Top Choice, Prime, Dark Cutter, Grass-fed, and Wagyu) were collected to achieve variation in fat content, sensory attributes, tenderness, and production background. Sections were aged for 14 d, fabricated into 2.54 cm thick steaks, and frozen until analysis. Trained descriptive panel rated tenderness, flavor, and juiciness attributes for sensory prediction models. Slice shear force (SSF) and Warner-Bratzler shear force (WBS) values were measured to predict tenderness classifications. A molecular fingerprint of each sample was collected via REIMS to build prediction models. Models were built using 80% of samples that were selected randomly for this purpose and tested for prediction accuracy using the remaining 20%. Partial least squares (PLS) discriminant analysis was used as a dimension reduction technique before building a linear discriminant analysis (LDA) model for classification. When Select and Low Choice samples, as well as Top Choice and Prime samples, were combined, balanced prediction accuracy reached 83.8%. Slice shear force and WBS tenderness classifications (tough vs tender) were predicted with 75.0% and 70.2% accuracy, respectively. Sensory models were built to assign samples into positive and negative classifications based on either all sensory attributes (i.e., tenderness, juiciness, and flavor) or only flavor attributes. Overall sensory class was predicted with 75.4% accuracy and flavor class with 70.3%. With future fine-tuning, these data suggest that REIMS produces a metabolic fingerprint to provide a method to meaningfully predict numerous beef quality attributes in an on-line application. The objective of the second study was to evaluate the roles of cooking rate and relative humidity on sensory development of beef strip steaks. Thirty USDA Choice beef strip loins were collected from a commercial packing facility. Each strip loin was cut into steaks and randomly assigned to 1 of 6 cooking methods utilizing 2 oven temperatures (80°C and 204°C) and 3 levels of relative humidity [zero (ZH), mid (MH), and high (HH)]. Cooked steaks were used to evaluate internal and external color, Warner-Bratzler and slice shear force, total collagen content, protein denaturation, and trained sensory ratings. Relative humidity greatly reduced cooking rate, especially at 80°C. Steaks cooked at 80°C-ZH had the greatest (P < 0.01) cook loss of all treatments, and cook loss was not affected (P > 0.05). Steaks cooked at 80C-ZH appeared the most (P < 0.01) well-done and had the darkest (P > 0.01) surface color. Total collagen was greatest (P < 0.01) in steaks cooked with ZH, regardless of oven temperature. Myosin denaturation was not affected (P > 0.05) by treatment. Increased (P = 0.02) sarcoplasmic protein denaturation was observed with ZH and MH, while increased (P = 0.02) actin denaturation was observed only with ZH. Oven temperature did not influence (P > 0.05) protein denaturation. Trained panelists rated steaks most tender (P < 0.01) when cooked at 80°C and with ZH and MH. Humidity did not affect (P > 0.05) juiciness at 204°C; however, MH and HH produced a juicier (P < 0.01) steak when cooked at 80°C. Humidity hindered (P < 0.01) the development of beefy/brothy and brown/grilled flavors but increased (P = 0.01) metallic/bloody intensity. Lower oven temperatures and moderate levels of humidity could be utilized to maximize tenderness, while minimally affecting flavor development.